Multifaceted Effects of Extracellular Adenosine Triphosphate and Adenosine in the Tumor–Host Interaction and Therapeutic Perspectives - de Andrade Mello, Paola; Coutinho-Silva, Robson; Savio, Luiz Eduardo Baggio (Frontiers in Immunology, 2017)
Cancer is still one of the world’s most pressing health care challenges, leading to a high number of deaths worldwide. Immunotherapy is a new developing therapy that boosts patient’s immune system to fight cancer by modifying tumor-immune cells interaction in the tumor microenvironment (TME). Extracellular adenosine triphosphate (eATP) and adenosine (Ado) are signaling molecules released in the TME that act as modulators of both immune and tumor cell responses. Extracellular ATP and Ado activates purinergic type 2 (P2) and type 1 (P1) receptors, respectively, triggering the so-called purinergic signaling. The concentration of eATP and Ado within the TME are tightly controlled by several cell surface ectonucleotidases, such as CD39 and CD73, the major ecto-enzymes expressed in cancer cells, immune cells, stromal cells, and vasculature, being CD73 also expressed on tumor associated fibroblasts. Once accumulated in the TME, eATP boosts antitumor immune response, while Ado attenuates or suppresses immunity against the tumor. In addition, both molecules can mediate growth stimulation or inhibition of the tumor, depending on the specific receptor activated. Therefore, purinergic signaling is able to modulate both tumor and immune cells behavior and, consequently, the tumor-host interaction and disease progression. In this review, we discuss the role of purinergic signaling in the host-tumor interaction detailing the multifaceted effects of eATP and Ado in the inflammatory TME. Moreover, we present recent findings into the application of purinergic-targeting therapy as a potential novel option to boost anti-tumor immune responses in cancer.